2015
DOI: 10.14419/ijbas.v5i1.5408
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patient safety culture among psychiatric, general, and specialized hospitals of Tehran

Abstract: Patient safety culture (PSC) has been considered less than its significance within high risk health care facilities so far. The aim of this study was to firstly compare PSC among psychiatric, general, and critical/intensive care systems then, focus on common weaknesses between Middle East countries. The study design was cross-sectional which was executed by using of a two stage sampling frame. Researchers had 298 questionnaire completed (RR=62%) among three groups comprising nurses, nurse's aides, and laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
3
0
1
Order By: Relevance
“…When it was used in different cultures, HSOPSC showed an acceptable fit of all dimensions and showed good construct validity (Vlayen, et al ). When it was used in different settings, HSOPSC showed similar weakness and strengths in all settings, implying that PSC perceived similarly by nurses working in mental health settings and both specialized and general settings and that HSOPSC was valid and reliable to be used in psychiatric setting (Raeissi & Shakibaei ). Also, the items and dimensions of HSOPSC were psychometrically sound at unit and hospital levels, implying that the researchers could use it to asses PSC in different settings (Sorra & Dyer, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When it was used in different cultures, HSOPSC showed an acceptable fit of all dimensions and showed good construct validity (Vlayen, et al ). When it was used in different settings, HSOPSC showed similar weakness and strengths in all settings, implying that PSC perceived similarly by nurses working in mental health settings and both specialized and general settings and that HSOPSC was valid and reliable to be used in psychiatric setting (Raeissi & Shakibaei ). Also, the items and dimensions of HSOPSC were psychometrically sound at unit and hospital levels, implying that the researchers could use it to asses PSC in different settings (Sorra & Dyer, ).…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of this study, HSOPSC was chosen because it is the most widely used and tested in different cultures, languages, setting and healthcare workers. For example, this instrument has been used and tested in many settings including specialized, general and psychiatric hospitals (Raeissi & Shakibaei ) and in different culture (Vlayen, et al ). When it was used in different cultures, HSOPSC showed an acceptable fit of all dimensions and showed good construct validity (Vlayen, et al ).…”
Section: Introductionmentioning
confidence: 99%
“…23 In terms of natural disasters, the social community collapses, and especially vulnerable people such as cancer patients are affected more compared with the other parts of the population. 24 Patients with chronic conditions such as diabetes, respiratory diseases, cancer, and cardiovascular diseases are the most vulnerable patient groups during natural or man-made disasters. 25,26 In a meta-analysis, it was observed that natural disasters have negative effects on cancer care, and it is advised to have special precautions for oncology patient care and infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Sendo assim, acredita-se que esta cultura deva ser constituída em todos os níveis de atenção à saúde, com especial direcionamento aos serviços de oncologia, já que o tratamento oncológico também pode envolver medidas mais invasivas que tornam os pacientes mais vulneráveis, tanto à ocorrência de erros e eventos adversos em saúde, como à piora da qualidade de vida e sentimentos relacionados à morte, além dos profissionais de saúde que atuam nesses setores estarem sob alto risco de esgotamento (FERMO et. al., 2015;RAEISSI et. al., 2017).…”
Section: Introductionunclassified